Lists of collections of the National Library of Wales - National Library of Wales
Typewritten lists of the library's manuscript collections relating to the coal and slate industries in Wales.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Coal industry -- Wales -- History -- Sources; Slate industry -- Wales -- History -- Sources